A one‐step way to novel carbon‐niobium nitride nanoparticles for efficient oxygen reduction. Issue 2 (24th October 2016) - Lin, Sen; Bi, Ke; Pan, Xiaolong; Hao, Yanan; Du, Yinxiao; Liu, Jun; Fan, Dongyu; Wang, Yonggang; Lei, Ming
Abstract: In recent years, researchers have been exploring various Pt‐free electrocatalysts to optimize the performance of regenerative fuel cell and rechargeable metal‐air battery. However, similar studies in ceramic fields are still stalled. In this work, as an efficient oxygen reduction reaction (ORR) catalyst, carbon‐niobium nitride (C‐NbN) nanostructure was successfully synthesized via a facile solid phase method. Microstructure characteristic analysis include SEM, TEM and element mapping spectra visually demonstrated C‐NbN nanoparticles, and its unique carbon coating layer. Moreover, the state of the carbon layer of C‐NbN was investigated by X‐ray photoelectron spectroscopy (XPS), Raman scattering spectrum, and energy‐dispersive X‐ray spectroscopy (EDX). After a series of electrochemical tests, it was found that such a novel carbon layer play two important roles in the ORR, leading to superior ORR performance (with 0.9 V onset potential, vs RHE) and outstanding durability (retained 97.02% of initial current for a duration of 10 000 second chronoamperometry test and excellent methanol tolerance) of C‐NbN catalyst. This method might could be implemented in the synthesis of other carbon‐transition nitride ceramics to enhance their ORR performance.